Simultaneous removal of fluoride and Fe (II) ions from drinking water by electrocoagulation. Issue 1 (February 2020) - Das, Daisy; Nandi, Barun Kumar
Graphical abstract: Abstract: Present work reports experimental investigations on simultaneous removal of fluoride and Fe (II) ions from drinking water by electrocoagulation (EC) with aluminium electrode having submerged electrode surface area of 116 cm 2 . During experimental studies, effects of pH, current density (Cd ), inter-electrode distance (Id ) and NaCl dose (Csi ) were investigated to identify their influence on fluoride and Fe(II) ions removal efficiency. Experimental results infer that pH of 7.0, Cd of 4.31 mA cm −2, Id at 1.0 cm and Csi of 0.33 g L −1 are ideal for highest removal of fluoride and Fe(II) ions from water. Overall, 96 % of fluoride ions and 98.88 % of Fe(II) ions were removed after 60 min of EC. Further it was observed that, presence of Fe (II) increases fluoride removal efficiency and fluoride ions increases Fe (II) removal efficiency. Different other impurities of water such as salinity, TDS, conductivity, turbidity were also decreased in treated water. Kinetic analysis infers that, for same operating condition Fe (II) removal rate (k = 0.0766 min −1 ) is higher compare to fluoride removal rate (k = 0.0535 min −1 ). Present study confirmed that EC is an efficient method for simultaneous removal of fluoride and Fe(II) ions along with other impurities with energy consumption of 1.716 KWh m −3 .